1999
DOI: 10.1111/j.1349-7006.1999.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Magnetic Particles on Radiofrequency Capacitive Heating

Abstract: Magnetic particles (magnetite) were used to make radiofrequency (RF) capacitive hyperthermia effective to a specific site. In an agar phantom experiment, a magnetite-containing agar piece was buried in a large agar phantom and heated by an 8 MHz-RF capacitive heating device. The magnetite-containing agar piece was heated more than the magnetite-free agar phantom, and the specific adsorption rate in the phantom was increased 1.5 times by the magnetite particles. The temperature distribution in the large agar ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The lower pH within the endosome allows an easy passage for the drug release into the target area. Magnetite cationic liposomes (MCLs), one of the groups of cationic magnetic particles, can be used as carriers to introduce magnetite nanoparticles into target cells since their positively charged surface interacts with the negatively charged cell surface; furthermore, they find applications in diverse hyperthermic treatments [9,11,13]. Magnetite nanoparticles conjugated with antibodies (antibody-conjugated magnetoliposomes, AMLs) have enabled tumour-specific contrast enhancement in MRI via systemic administration.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower pH within the endosome allows an easy passage for the drug release into the target area. Magnetite cationic liposomes (MCLs), one of the groups of cationic magnetic particles, can be used as carriers to introduce magnetite nanoparticles into target cells since their positively charged surface interacts with the negatively charged cell surface; furthermore, they find applications in diverse hyperthermic treatments [9,11,13]. Magnetite nanoparticles conjugated with antibodies (antibody-conjugated magnetoliposomes, AMLs) have enabled tumour-specific contrast enhancement in MRI via systemic administration.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
“…al. [11] demonstrated that magnetic nanoparticles serve as a medium that induces efficient heat generation in RFcapacitive heating. In an in-vivo experiment, they observed that heat generation using magnetic nanoparticles was similar to that using inductive heating employing an alternating magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of tumor inhibition was performed using the calculating tumor volume according to the following formula 10,11 :…”
Section: Morphological Evaluation In Tumor Inhibitionmentioning
confidence: 99%